2009
DOI: 10.1002/adma.200801498
|View full text |Cite
|
Sign up to set email alerts
|

Calcite Growth in Hydrogels: Assessing the Mechanism of Polymer‐Network Incorporation into Single Crystals

Abstract: Synthetic and biogenic calcite (CaCO 3 ) crystals are known to incorporate biomacromolecules [1] and other organic molecules [2] while still diffracting x-rays as single crystals. This work evaluates the parameters that control the incorporation of polymer networks during calcite-crystal growth in agarose hydrogels. We find that the crystallization pressure promotes the exclusion of the gel network, while faster growth rates favor the incorporation. These two competing factors determine how much of the gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
204
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(218 citation statements)
references
References 31 publications
10
204
2
2
Order By: Relevance
“…One possibility to explain the similar fluorescence and C-H bonding between abiogenic aragonite and coral skeleton is that organic matter from seawater is trapped in growing aragonite crystals (Benzerara et al, 2011). Tendencies toward higher organic indices with increasing Ar (Figures 5A-C, r 2 between 0.24 and 0.56) may suggest this organic trapping mechanism increases under more rapid crystal growth as has been observed previously for calcite (Li and Estroff, 2009), but this interpretation remains inconclusive due to the lack of statistically significant correlations between the metrics and Ar (0.05 < p < 0.10).…”
Section: Discussion Organic Matter In Abiogenic and Coral Samplesmentioning
confidence: 52%
See 1 more Smart Citation
“…One possibility to explain the similar fluorescence and C-H bonding between abiogenic aragonite and coral skeleton is that organic matter from seawater is trapped in growing aragonite crystals (Benzerara et al, 2011). Tendencies toward higher organic indices with increasing Ar (Figures 5A-C, r 2 between 0.24 and 0.56) may suggest this organic trapping mechanism increases under more rapid crystal growth as has been observed previously for calcite (Li and Estroff, 2009), but this interpretation remains inconclusive due to the lack of statistically significant correlations between the metrics and Ar (0.05 < p < 0.10).…”
Section: Discussion Organic Matter In Abiogenic and Coral Samplesmentioning
confidence: 52%
“…We plotted these metrics against fluid Ar in order to (1) visualize any differences among samples, and (2) assess whether organic matter content correlates with Ar , which could indicate that more organic molecules are trapped in faster growing crystals (Perrin and Smith, 2007;Li and Estroff, 2009;Benzerara et al, 2011). There was a general tendency of increasing fluorescence with Ar in abiogenic samples (Figure 5A), but the large variance within samples precludes any definitive interpretations and the pattern was not significant [r 2 = 0.56, n = 7, p = 0.053, F (1, 5) = 6.397].…”
Section: Resultsmentioning
confidence: 99%
“…Properties of the gel matrix such as density, porosity, mechanical stress and chemical nature have a significant bearing on crystal growth. For instance, calcite crystals grown in agarose hydrogels incorporate gel structures depending on the kinetics of crystal growth and the gel strength of the media (Li and Estroff 2009). A weak gel of agarose is pushed away by the growth fronts of the crystal, whereas a strong gel resists deformation, leading to calcite crystals that grow around and incorporate the fibers.…”
Section: Mineralization In Matrices and Gelsmentioning
confidence: 99%
“…On the other hand, the incorporation of polymer networks into the calcium carbonate single crystals follows different mechanisms from the incorporation of particles. Li et al studied the occlusion of 3D agarose hydrogel into the single crystals of calcium carbonate and found that besides the gel concentration and the rate of the crystal growth, the strength of hydrogel was also an important factor for either complete incorporation of gel network into the crystal lattice or total exclusion of the gel material from the crystal structure [30]. Using annular dark-field scanning TEM, they were able to visualize the 3D structure of hydrogel networks inside the single crystals.…”
Section: Introductionmentioning
confidence: 99%